Role of Delayed Feedback and Graphene Saturable Absorber in Cavity Soliton - Kaur, Ramanpreet (My University, 2019)
The formation of localized structure in wide area nonlinear cavity has been investigated. Analytical as well as numerical methods have been adopted to determine the evolution of the localized structures. Cavity soliton have been generated with different delayed feedback. The influence of delay is compared with the case of no delay in feedback. The phase portraits have been drawn and analyzed to identify the center of the localized structure, i.e., cavity soliton. The nonlasing zone has also been identified. The whole investigation on cavity soliton has been carried out in two parallel situations; with and without graphene saturable absorber. The influence of graphene has been identified. Applications of the result of the present investigation have been suggested.
MSc Thesis
Keywords: Cavity soliton; delayed feedback; Graphene; saturable absorber